4D PET/CT as a Strategy to Reduce Respiratory Motion Artifacts in FDG-PET/CT - Chi, Alexander; Nguyen, Nam P. (Frontiers in Oncology, 2014)
18F fluorodeoxyglucose positron emission tomography (FDG-PET) has changed the staging of, and the treatment response assessment for lung cancer over the past decades dramatically. The improved accuracy in tumor identification with FDG-PET has led to its increased utilization in target volume delineation for radiotherapy treatment planning in the treatment of lung cancer. Despite the increased ability to distinguish tumor and normal tissue with the help of PET/CT registration, how to best delineate the PET avid tumor volume continues to be controversial as the PET intensity can be influenced by multiple machine and patient related factors. One major factor influencing the PET intensity and image resolution in the thorax is respiratory motion. This problem may be minimized by 4D FDG-PET based treatment planning, which can further improve the resolution of tumor extent, and the delineation of the internal target volume. Here, we offer our perspectives on the utilization of 4D FDG-PET based treatment planning for thoracic image-guided radiotherapy.